Chemistry Learning Media Based on Social Media: Students’ View - Sri Yamtinah; Ari Syahidul Shidiq; Hayuni Retno Widarti; Mawardi Mawardi (Postgraduate, University of Mataram, 2023)
Chemistry learning should be able to integrate contextual chemistry problems and present the sophistication of 21st-century learning technology. Social media, as a product of 21st-century technology, has the potential to be used as chemistry learning media. Therefore, this study aims to investigate students’ views toward the potential use of social media as chemistry learning media. The survey method involved 791 students. A total of 40 question items were developed and distributed online using a Google form to respondents. Based on the results of a survey conducted, it is known that respondents are accustomed to using Instagram and TikTok as the most frequently used social media. Other results reveal that most respondents have the same screen time, more than 4 hours daily. This screen time is used by respondents for entertainment and looking for news information on social media. With the length of screen time not used for this learning process, it can be a promising opportunity to utilize social media as a medium for learning chemistry. This study is expected to be a reference for developing social media-based chemistry learning to increase student motivation and achievement.